Poverty in India Has Declined over the Last Decade But Not As Much As Previously Thought - Sinha Roy, Sutirtha (World Bank, Washington, DC, 2022)
The last expenditure survey released by India’s National Sample Survey organization dates back to 2011, which is when India last released official estimates of poverty and inequality. This paper sheds light on how poverty and inequality have evolved since 2011 using a new household panel survey, the Consumer Pyramids Household Survey conducted by a private data company. The results show that: (1) extreme poverty is 12.3 percentage points lower in 2019 than in 2011, with greater poverty reductions in rural areas; (2) urban poverty rose by 2 percentage points in 2016 (coinciding with the demonetization event) and rural poverty reduction stalled by 2019 (coinciding with a slowdown in the economy); (3) poverty is estimated to be considerably higher than earlier projections based on consumption growth observed in national accounts; and (4) consumption inequality in India has moderated since 2011.